(3JRjf bdGFO GdYbjGf ddaJM Hf NGbGfs - (3eMeO Hf bGSe Hf eMeO Hf YHO GdhGMO GdaGSj, CHh YHO Gddg, GHf RGchQ , J (B1120 (3g` s; (3GdaJM Hf eMeO Hf YHjO Gddg Hf NGbGf GHf YHO Gddg GdbjSj, CHh fU,J (B528 (3g` s
(3BNQgG (B:s
(3Ci CcKQ HOGYI , HaJM GdHGA GdehMOI GdJMJjI , HOhYG, HGdOGd GdegedI HYOgG, HoOY ccQe , EPG UGQ HOjYkG s
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B134 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B49s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B110 s
Keywords: (3GdJGQjNs